Multimedia-Based Learning Media Development - Putri Enita; Ahmad Musthafa; Rapida Hasanah (Proceeding International Seminar of Islamic Studies, 2019)
One that can facilitate students in understanding the subject matter is the use of instructional media. Currently the most widely used multimedia learning media, it is due to its ease, flexibility, and efficiency. But not all teachers can easily develop this multi-media-based learning media. Lack of understanding in designing it is a major factor, in addition to other factors, namely inadequate school facilities and facilities. Religious learning certainly cannot be understood as learning based on the totality of lectures, but it would be more interesting if it was developed using multimedia-based media for example. This paper aims to analyze: (1) Characteristics of PAI learning and its suitability with multimedia-based learning media, (2) Skills and Techniques for developing multimedia-based learning media, (3) Barriers to teachers in developing multi-media-based learning media. This study uses qualitative research methods using a descriptive analysis approach. Data collection techniques are done by observation, interviews, and study documentation. This research was conducted at Al-Fattah Middle School Medan, for 2 months, and with a total of 10 informants. The results of the study show that: (1) Islamic religious education learning has characteristics not much different from other learning namely there is a load of cognitive, affective, and psychomotor aspects, so it is very necessary learning media that is able to accommodate all the demands of learning objectives as the taxonomy of learning above (2) Not all teachers are able to use multimedia-based learning media, only a part of it (3) The mindset about learning media as an alternative in learning is the main factor in the lack of use of instructional media, in addition to other factors due to lack of development.